Down-regulation of glutamate release from hippocampal neurons by sialidase. (8th January 2018) - Minami, Akira; Ishii, Ami; Shimba, Sumika; Kano, Takahiro; Fujioka, Eri; Sai, Saki; Oshio, Nagisa; Ishibashi, Sayaka; Takahashi, Tadanobu; Kurebayashi, Yuuki; Kanazawa, Hiroaki; Yuki, Nobuhiro; et al.
Abstract: Sialidase, which removes sialic acid residues in sialylglycoconjugates, is essential for hippocampal memory and synaptic plasticity. Enzyme activity of sialidase is rapidly increased in response to neural excitation. Because sialic acid bound to gangliosides such as the tetra-sialoganglioside GQ1b is crucial for calcium signalling and neurotransmitter release, neural activity-dependent removal of sialic acid may affect hippocampal neurotransmission. In the present study, we found that 2-deoxy-2, 3-didehydro-D- N -acetylneuraminic acid (DANA), a sialidase inhibitor, increased expression of ganglioside GQ1b/GT1a in hippocampal acute slices. Extracellular glutamate level in the rat hippocampus measured by using in vivo microdialysis was increased by the sialidase inhibitor 2, 3-dehydro-2-deoxy- N -glycolylneuraminic acid as well as DANA. Synaptic vesicle exocytosis and intracellular Ca 2+ increase evoked by high-K + were also enhanced by DANA in primary cultured hippocampal neurons. Expression of GQ1b/GT1a was rapidly decreased by depolarization with high-K +, suggesting that the increase in sialidase activity by neural excitation is sufficient for cleavage of sialic acid. Our findings indicate that sialidase down-regulates glutamate release from hippocampal neurons via Ca 2+ signalling modulation. Neural activity-dependent desialylation by sialidase may be a negative-feedback factor against presynaptic activity.